A Stationary-Frame Current Vector Control Strategy for Single-Phase PWM Rectifier - Zhang, Chengxiang; Yu, Siru; Ge, Xinglai (IEEE transactions on vehicular technology, 2019)
Traditional current control methods for a single-phase rectifier in an electric traction drive system suffer from either long response time or nonzero steady-state error. A novel current vector control strategy in stationary-frame is therefore proposed, in this paper, to improve the control performance of a rectifier. The mathematic model of the single-phase two-level pulse rectifier was first analyzed by complex space vector. Then, the principle of the proposed current control method was described. Based on this, the implementation and parameter tuning method of the current control algorithm based on a space complex vector in a two-phase stationary coordinate system are presented. Moreover, two kinds of general current control algorithms are analyzed and compared with the proposed algorithm to demonstrate the advantages of the proposed algorithm. The proposed control scheme absorbs advantages of the conventional control schemes, including fast response, zero steady-state error, and active and reactive power independent control, but overcomes their shortcomings. Finally, the theoretical analysis is verified by means of simulation as well as a hardware-in-loop experimental test on an experimental laboratory setup and some comparisons with conventional current control algorithms prove the advantages of the utilized method.